The relationship between college students’ autonomous fitness behavior and mental health literacy: chain mediating effect test - Chen, Chunping; Wang, Bin (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to explore the effect of autonomous fitness behavior on college students’ mental health literacy, and the mediating roles of self-control and exercise identity.MethodologyA cross-sectional survey using cluster sampling was conducted among 974 college students from Shandong Province, China. Data on autonomous fitness behavior, mental health literacy, self-control, and exercise identity were collected using standardized scales (Cronbach’s α: 0.722–0.949). SPSS 26.0 (PROCESS Macro Model 6) and AMOS 26.0 were used for statistical analyses, including correlation, regression, and mediation effect tests with 5,000 Bootstrap samples.Results(1) Autonomous fitness behavior positively predicted mental health literacy (β = 0.416, p < 0.001), self-control (β = 0.301, p < 0.001), and exercise identity (β = 0.198, p < 0.001); self-control also positively predicted exercise identity (β = 0.281, p < 0.001). (2) Three significant indirect paths were identified: ① Autonomous fitness behavior → Self-control → Mental health literacy (indirect effect = 0.024, 95% CI [0.008, 0.042], accounting for 5.77% of total effect); ② Autonomous fitness behavior → Exercise identity → Mental health literacy (indirect effect = 0.155, 95% CI [0.122, 0.189], accounting for 37.25% of total effect); ③ Autonomous fitness behavior → Self-control → Exercise identity → Mental health literacy (indirect effect = 0.066, 95%CI[0.049, 0.084], accounting for 15.87% of total effect). The total indirect effect was 0.245 (95% CI [0.210, 0.279]).ConclusionAmong the surveyed college students, autonomous fitness behavior influences mental health literacy directly and indirectly through the independent mediating effects of self-control and exercise identity, as well as their chain mediating effect. These findings provide preliminary evidence for the mechanism linking autonomous fitness behavior to mental health literacy, which may inform targeted mental health interventions in higher education settings.